Impact of Job Satisfaction on Job Performance with Reference to Public Banks in Sri Lanka - Jayarathna, S.M.D.Y. (Staff Development Center, University of Kelaniya, 2015)
To attain a competitive advantage and remain in the competitive market, organizations should focus on the employee job satisfaction and job performance. Job Satisfaction is one of the most significant attitudes of the employees of an organization and it describes whether the employees are happy, asserted, and fulfilling their desires and needs at work. The organizations are challenged, as they have to make the employee’s satisfied in their job. So, they will perform better and consequently organization will achieve their competitive edge. Thus, achieving job performance of the employees has been significant for both private and public organizations. Hence, it is needed to investigate how the satisfaction of the employees of the public banks affects the job performance of their employees. As such, the objective of this research is to investigate the impact of job satisfaction on job performance of the public banks in Colombo District. The independent variable of the study is job satisfaction and the dependent variable is job performance. The reliability of the instruments are to be tested against the survey data. This study focuses on hypothesis testing and is a correlational study. The research is to be conducted in the natural environment where work proceeds normally, with less interference of the researchers (non contrived setting). Data will be collected from individuals: employees of the public banks, and the study is cross sectional. The population of the study will be Managerial, Executive and Non Executive employees in the public banks operating in Colombo district of Sri Lanka. It is expected to collect data by distributing from 400 self administered anonymous questionnaires. Data used for the analysis will be primary data. The analysis will be done by simple regression models using the software SPSS 20.0.
Keywords: Job Satisfaction; Job Performance; Public Banks